MUSLIM & MODERN INVENTORS OF THE CAMERA IN THE HISTORY OF PHYSICS - Roprop Latiefatul Millah; Dedi Kuntadi; Adam Malik (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2022)
Camera technology can help support human activities, especially in the digital era. The first Muslim scientist who invented the camera was Ibn al-Haitham, where the mechanism of the way of capturing images is currently also used and applied to become a sophisticated camera with high quality and resolution. This research aims to discover how Muslim scientists' role in discovering camera technology and modern scientists' role in ancient times until this camera technology supports the historical development of physics, especially in optics. This historical research uses secondary data sources through literature. The study's results using the interpretation of data obtained from various references obtained from various relevant references indicate that the invention of the camera was initiated by Muslim scientist Ibn Al Haitham who later modern scientists also improved and developed theory. The application of camera optics to create camera technology that is helpful for life and human activities.